An Archaeological Challenge: The Conservation and Restoration of Luxury Roman Glass from Troia, Portugal - Inês Coutinho; Beatriz Borges; Stephen Koob (Heritage, 2025)
A set of eleven luxury glass archaeological objects dated to the 3rd century (Roman period) and excavated in Troia, Portugal, were treated in order to restore their shapes and decorative features. In this paper, the different stages of the treatment are presented and discussed. The treatment phases—cleaning, fragments’ assembly, and development of support structures for the objects in need—had to be adapted and the treatment outline had to be revised along the process because of the heavily weathered glass that showed extreme fragility. The treatment highlights the internal support structures—consisting of thin and light structures built with thin canes of glass—that were developed in borosilicate glass for three of the archaeological objects, ensuring their physical stability for handling and future exhibition. The structures were then attached to the archaeological glass with Paraloid B72 adhesive. The treatment of these outstanding artefacts and, in particular, the development of these structures heavily depended on interdisciplinary and teamwork that resulted in the completion of the treatment for all objects ensuring their future exhibition.